A NEW UZBEKISTAN CANNOT BE FORMED THROUGH THE OLD ACCOUNTING SYSTEM, OR THE HARMONIZATION OF THE ACCOUNTING SYSTEM WITH INTERNATIONAL STANDARDS - Barakayev Otabek Otaqulovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the necessity of reforming Uzbekistan’s accounting system to align with international standards as part of the country’s broader economic modernization and integration into the global market. It argues that the old accounting framework, inherited from a centrally planned economy, no longer meets the demands of a dynamic, market-oriented environment. The study highlights the importance of transparency, comparability, and reliability of financial information, emphasizing that harmonization with International Financial Reporting Standards (IFRS) is a crucial step toward building investor confidence, improving corporate governance, and fostering sustainable economic growth. The article concludes that a “New Uzbekistan” can only be realized through the transformation of its accounting system in line with international best practices.